Pendampingan Pastoral Konseling Kepada Anak Putus Sekolah Dengan Pendekatan Client-Centered (Berpusat pada klien) dan Rasional Emotif Behavior Therapy (Terapi perilaku rasional-emotif) Agar Percaya Diri - Juliana Waruwu; Rencan Carisma Marbun (Sukacita : Jurnal Pendidikan Iman Kristen, 2025)
Children who do not want to go to school and cannot complete their schooling and cannot finish their schooling or in other words do not get a diploma. There are various reasons why children can drop out of school, such as lack of attention from parents, economic problems, low interest in going to school, helping parents at work, being involved in juvenile delinquency cases, low intelligence levels, socialization and also the school zoning system. The purpose of the observation is to obtain information from the consequences of the child leaving school and to help the child to accept himself that he is a child who dropped out of school, so as not to be inferior and lose hope and convince the client (counselee) that the counselee can return to school and achieve his goals. This observation uses a qualitative method, in this case collecting data about events or phenomena that occur, and using a client-focused approach (psychotherapy that focuses on the client to solve his own problems), the counselor's presence is to listen empathetically and be fully present, and a rational-emotive behavioral therapy approach (an approach that aims to help someone overcome emotional disturbances and think rationally). From the results of the study, pastoral counseling assistance with a client-centered approach and rational emotive behavior therapy can help people who drop out of school not lose confidence, if they see their peers going to school, can open up, be more diligent in worship and more eager to prepare themselves to return to school.